Основные периоды существования христианства у гагаузов Буджака и их оценка с исторической точки зрения. - Hatłas, Jerzy (My University, 2009)
Etapele principale de răspândire a credinţei creştine la găgăuzii din Bugeac sunt legate de organizarea statală a teritoriului său (şi al Basarabiei). Au fost identifi cate următoarele etape: I. Imperiul Rus şi Principatul Moldovei, II. Statul român (1918-1940 şi 1941-1944), III. Puterea sovietică (1940-1941 şi 1944-1991), Republica Moldova şi Ucraina. Credinţa creştină a fost practicată atât sub Imperiul Rus cât şi în timpul statului român. În Moldova şiUcraina contemporană există de asemenea şi alte mişcări religioase (datorită standardelor internaţionale). Unica excepţie o constituie perioada sovietică atunci când religia a fost combătută prin impunerea ateismului în regiunea Bugeac locuită de găgăuzi.

The main periods of Christian faith development among the Gagauzians living in the Bugeac are connected with state organization of this territory (and Bessarabia). The following periods can be identifi ed: I. Russian Empire and Moldovan Principality, II. The Romanian state 1918-1940 and 1941-1944, III The Soviet power (1940-1941 and 1944-1991), Republic of Moldova and Ukraine. The Christian faith functioned both under the Russian Empire and during the Romanian state. There are in the contemporary Moldova and Ukraine some new religious movements (according to the international standards). The only exception is the soviet period when the religion has been represses in favor of atheism in the area of Bugeac, inhabited by Gagauzians.
The main periods of Christianity at the Gagauzians in the Bugeac – the historical point of view and its evaluation
Keywords: Cerkiew prawosławna; Gagauzia; Religia; Mołdawia